Investigation of a Case of Genotype 5a Hepatitis C Virus Transmission in a French Hemodialysis Unit Using Epidemiologic Data and Deep Sequencing. (29th October 2015) - Aho-Glélé, L. S.; Giraudon, H.; Astruc, K.; Soltani, Z.; Lefebvre, A.; Pothier, P.; Bour, J. B.; Manoha, C.
Abstract : BACKGROUND: Hepatitis C virus (HCV) is a major cause of chronic liver disease worldwide. A patient was recently found to be HCV seropositive during hemodialysis follow-up. OBJECTIVE: To determine whether nosocomial transmission had occurred and which viral populations were transmitted. DESIGN: HCV transmission case. SETTING: A dialysis unit in a French hospital. METHODS: Molecular and epidemiologic investigations were conducted to determine whether 2 cases were related. Risk analysis and auditing procedures were performed to determine the transmission pathway(s). RESULTS: Sequence analyses of the NS5b region revealed a 5a genotype in the newly infected patient. Epidemiologic investigations suggested that a highly viremic genotype 5a HCV-infected patient who underwent dialysis in the same unit was the source of the infection. Phylogenetic analysis of NS5b and hypervariable region-1 sequences revealed a genetically related virus (>99.9% nucleotide identity). Deep sequencing of hypervariable region-1 indicated that HCV quasispecies were found in the source whereas a single hypervariable region-1 HCV variant was found in the newly infected patient, and that this was identical to the major variant identified in the source patient. Risk analysis and auditing procedures were performed to determine the transmission pathway(s). Nosocomial patient-to-patient transmission via healthcare workers' hands was the most likely explanation. In our dialysis unit, this unique incident led to the adjustment of infection control policy. CONCLUSIONS: The data support transmission of a unique variant from a source with a high viral load and genetic diversity. This investigation also underlines the need to periodically evaluate prevention and control practices. Infect. Control Hosp. Epidemiol. 2016;37(2):134–139